Invasive species of Ceratium Schrank, 1973 (Dinophyceae: Ceratiaceae) in freshwater bodies from Peru - Mendoza-Carbajal, Leonardo (2022)
This works provides information on the presence in Peru of two invasive species of the genus Ceratium: C. hirundinella (O.F. Müller) Dujardin and C. furcoides (Levander) Langhans. Information is provided on the distribution of both species in Peruvian water bodies, as well as data on their abundance.